2020
DOI: 10.1051/matecconf/202031904003
|View full text |Cite
|
Sign up to set email alerts
|

Process Control Improvement in Deep Drawing of Hemispherical Cups Made of GLARE Material

Abstract: Controlling the material flow under the blank holder in hydroforming is a delicate point that can be controlled by the blank holder force (BHF), cavity pressure (CP) and the blank holder gap (BHG). BHG is one of the effective parameters to control the material flow. A numerical and experimental approach studied the impact of the BHG on the Hydromechanical Deep Drawing (HDD) of a hemispherical cup made with 2/1 Glare sheets, including another two factors, CP and BHF. BHGs with different thickness was used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The measured results for the same PR, BHP, and T, but the different lengths of 2B were plotted in the same coordinate system and the limiting strain of pure aluminum and fiber were also plotted. Similarly, the results of aluminum were also obtained through the HBT, while the results of prepreg could be calculated according to its maximum elongation (4.80%) [9]. Thus, a typical FLC with PR = 0.1, T = 20, and BH P= 14 was drawn as shown in Figure 4.…”
Section: Establishment Of Comprehensive Flcmentioning
confidence: 99%
“…The measured results for the same PR, BHP, and T, but the different lengths of 2B were plotted in the same coordinate system and the limiting strain of pure aluminum and fiber were also plotted. Similarly, the results of aluminum were also obtained through the HBT, while the results of prepreg could be calculated according to its maximum elongation (4.80%) [9]. Thus, a typical FLC with PR = 0.1, T = 20, and BH P= 14 was drawn as shown in Figure 4.…”
Section: Establishment Of Comprehensive Flcmentioning
confidence: 99%
“…Recently, these forming methods were utilised to form steel-based FMLs, but the latest research papers have been focused mainly on aluminium-based composites. Researchers consider the configuration of the material layers [374][375][376][377] or the process parameter setup [86,[378][379][380][381][382][383][384][385][386] to reduce material defects and go beyond the current forming limits caused mainly by breakage and wrinkling. In order to improve the formability of the layers of FRP, many studies are focused on die forming at elevated temperatures [387][388][389].…”
Section: Die Formingmentioning
confidence: 99%
“…Furthermore, a significant effect of blank holder force was noted, in that the selection of the higher forces (7 kN and 14 kN) affects wrinkling reduction, but a delamination effect was also observed. Additionally, Blala et al [378,379] performed drawing tests on 2/1 GLARE (0.5/0.2/0.5 mm) composite. Different blank holder forces, gaps, and cure states were considered.…”
Section: Stampingmentioning
confidence: 99%
“…Many investigations have been conducted to find the effective parameters during the forming process based on hydroforming. Recently, Blala H. et al, [7] presented an investigation into the process impact of the deep drawing process of hemispherical cups made with GLARE material. Their research revealed that BHG controls the material flow and also affects the drawing process and product quality.…”
Section: Introductionmentioning
confidence: 99%